Comparison of Poco-Poco GWR and Indonesian Asma Gymnastics to increasing vo2 max - Putri Cicilia Kristina; Endie Riyoko; Daryono Daryono; Siti Ayu Risma Putri; Perabu Nita (Universitas Sriwijaya, 2023)
This study aims to find out the comparison between the GWR poco-poco gymnastic exercise and the Indonesian Asthma Gymnastics exercise to increase the ability of Volume Oxygen Maximum (VO2max). The method used in this study is a pure experimental method (true experiment), while the research design used is the pre-test-post-test control group design. The population in this study were 16 students of Physical Education. The data collection technique for the VO2max test uses a Multi-Stage Test (Bleep Test). The data analysis technique uses Analysis of Variance (ANOVA). The results of this study indicate that there is a significant effect of Poco-poco Gymnastic exercises 31.94 > 2.31) and Indonesian Asthma Gymnastics exercises (33.92 > 2.31) on the ability to increase VO2max in Physical Education Students at PGRI Palembang University. The conclusion of this study is that Indonesian Asman exercises are better than Poco poco gymnastic exercises in increasing VO2max.Â